Safe migration and the politics of brokered safety in Southeast Asia (Taylor & Francis, 2021)
"The book investigates how the United Nations, governments and aid agencies mobilise and instrumentalise migration policies and programmes through a discourse of safe migration. Since the early 2000s, numerous non-governmental organizations (NGOs), UN agencies and governments have warmed to the concept of safe migration, often within a context of anti-trafficking interventions. Yet, both the policy-enthusiasm for safety, as well as how safe migration comes into being through policies and programs remain unexplored. Based on six years of ethnographic fieldwork in the Mekong region, this is the first book that traces the emergence of safe migration, why certain aid actors gravitate towards the concept, as well as how safe migration policies and programmes unfold through aid agencies and government bodies. The book argues that safe migration is best understood as brokered safety. Although safe migration policy interventions attempt to formalize pre-emptive and protective measures to enhance labour migrants' well-being, the book shows through vivid ethnographic details how formal migration assistance in itself depends on - and produces - informal, mediated practices. The book offers unprecedented insights into what safe migration policies look like in practice. It is an innovate contribution to contemporary theorizing of contemporary forms of migration governance and will be of interest to sociologists, anthropologists, political scientists and human geographers working within the fields of Migration studies, Development Studies as well as Southeast Asian and Global Studies. "
Australian Research Council
English
Keywords: Ethnic studies; Regional / International studies; brokered safety, politics, safe migration, Southeast Asia